Exergy analysis of a target drone engine: an experimental study for TRS18. (2018) - Aydin, Emre; Turan, Onder; Kose, Ramazan
This article examines exergetic performance of an experimental TRS18 turbojet engine built in Anadolu University Faculty of Aeronautics and Astronautics Test-Cell Laboratory. In the analysis, engine performance parameters (pressure, temperature, fuel and airflow, thrust force) are taken from the test-cell measurement devices. At the end of the work, total exergy efficiency of the target drone engine is obtained to be 42%. For TRS18, exergy destruction rate is 0.872 MW in the combustor due to the physical and chemical exergy destruction. For maximum exergy, destruction rate is obtained to be 0.872 MW in the combustor due to the physical and chemical exergy destruction, while it is 1.21 MW for the total for the engine. Improvement rates (IP) for combustion chamber, compressor and turbine are calculated to be 0.34 MW, 0.0025 MW and 0.007 MW, respectively. As a conclusion, it is expected that results from this study can be useful to future design, research and experimental works related to small turbojets, auxiliary power units and target drone power systems.